HUBUNG ANTARA KECERDASAN EMOSIONAL DAN KECERDASAN SPRITUAL DENGAN KEPUASAN KERJA GURU SEKOLAH DASAR NEGERI SE KECAMATAN DUMAI BARAT KOTA DUMAI - Weni, Weni; Saam, Zulfan; Azhar, Azhar (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study aims to determine the relationship between emotional intelligence and spiritual intelligence with teacher job satisfaction. This study uses a survey method with correlational techniques. The population of the study was the teachers of SDN in Dumai Barat District, Dumai City with a sample of 150 people. The instrument used for data collection is a number of written questions with 4 variations of answer choices. The instrument item validation was tested using product moment correlation, while the instrument reliability test was calculated using the Alpha Conhbach formula. The results showed that (1) there was a significant relationship between spiritual intelligence and job satisfaction of State Elementary School teachers in Dumai Barat District, Dumai City. (2). There is a very strong relationship between spiritual intelligence and job satisfaction of State Elementary School teachers in Dumai Barat District, Dumai City. (3). There is a positive and significant relationship between emotional intelligence and spiritual intelligence together with job satisfaction of State Elementary School teachers in Dumai Barat District, Dumai City. The results of this study are expected to be useful for improving work stress, emotional intelligence and personality of State Elementary School teachers in West Dumai District, Dumai City. The conclusion of this study shows that job satisfaction can be reduced through increasing emotional intelligence and spiritual intelligence either alone or together